Book review: Fagan, Jenni. (2012), The Panopticon. London: Windmill Books. 324 pp, ISBN-13: 9780099558644 ISBN: 0099558645 - Autumn Roesch-Marsh (Scottish Journal of Residential Child Care)
The Panopticon by Edinburgh poet and writer Jenni Fagan is not for the faint hearted. It is a novel about a 15-year-old girl named Anais who is living in a residential care home on the outskirts of a large Scottish city, and Jenni Fagan has been very open about the fact that it draws on some of her experiences of being in residential care. As someone who has worked in residential care, I recognised in Anais so many of the young women I have met in residential units. She is fierce and at times frightening and yet incredibly vulnerable and traumatised from a lifetime of abuse and loss. She is smart and resilient and at the same time her behaviour can be erratic and extremely dangerous to herself and others. Anais is the narrator of her own story and the story includes flashbacks to key moments in her life, including the murder of her foster mother and the loss of her best friend. When we meet Anais she has just spent the night in the police cells after attacking a police officer. Anais cannot remember exactly what happened as she was under the influence of drugs and alcohol at the time. As she approaches the front door of the residential home she says, 'My heart's going. I've moved fifty-one fucking times now, but every time I walk through a new door I feel exactly the same – two years old and ready tae bite' (p. 9). For me this description of feeling 'two years old and ready tae bite' encapsulates the way that so many children who have been shunted around the care system from an early age must feel on the inside. Having missed out on early nurture, security and love, their inner world often resembles that of an angry, uncontained toddler, desperate for love and care but biting out in terror and fear of further rejection, abuse and loss.